Hacia una historia visual de la fruticultura - Bariani, Julio (2018)
This work is developed around the graphic fruit growing in Alto Valle de Río Negro and Neuquén. It is an approach on the evolution and analysis of the diachronic development of the identifying elements —marks, symbols and logos and illustrations— in regional fruit growing. The focus is on the commercialization of pear and apple in a period that, although it covers approximately from the second quarter of the 20th century to the present day, it highlights the moment of greater development of fruit growing in the region: from 1940 to the mid-1970s.